Strategi Pengurus Asrama A Dalam Membentuk Karakter Mandiri Santri Di Pondok Pesantren Ngalah - Abdul Khamid; Muhammad Nur Hadi (Al-Abshor : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the strategies of Dormitory A administrators in developing independent character in students at the Ngalah Islamic Boarding School in Pasuruan. Independent character is one indicator of the success of Islamic boarding school education, encompassing discipline, responsibility, self-confidence, and the ability to make independent decisions. This study used a descriptive qualitative approach, with data collection techniques including interviews, participatory observation, and documentation. The research subjects were Dormitory A administrators and the students they care for. The results indicate that the strategies used by the administrators include establishing daily routines, providing motivation, direct supervision, and modeling attitudes. Supporting factors in developing independent character include the religious environment of the Islamic boarding school, the active role of mentors, and structured activities. However, obstacles also exist, such as the diverse backgrounds of the students, limited facilities, and a lack of internal motivation. The role of dormitory mentors is not only as supervisors but also as motivators and guides, shaping the students' character holistically. This research is expected to serve as a reference in developing character development programs in Islamic boarding schools and serve as a reference for other Islamic educational institutions in developing an independent and noble generation. Abstrak Penelitian ini bertujuan untuk menganalisis strategi pengurus Asrama A dalam membentuk karakter mandiri santri di Pondok Pesantren Ngalah, Pasuruan. Karakter mandiri merupakan salah satu indikator keberhasilan pendidikan pesantren yang mencakup kedisiplinan, tanggung jawab, kepercayaan diri, serta kemampuan mengambil keputusan secara mandiri. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara, observasi partisipatif, dan dokumentasi. Subjek penelitian adalah pengurus asrama A dan santri yang diasuh.Hasil penelitian menunjukkan bahwa strategi yang digunakan pengurus asrama mencakup pembiasaan kegiatan harian, pemberian motivasi, pengawasan langsung, dan teladan sikap. Faktor pendukung dalam pembentukan karakter mandiri di antaranya adalah lingkungan pesantren yang religius, peran aktif pembimbing, serta kegiatan terstruktur. Namun demikian, terdapat pula hambatan seperti latar belakang santri yang beragam, keterbatasan fasilitas, dan kurangnya motivasi dari dalam diri santri. Peran pembimbing asrama tidak hanya sebagai pengawas, tetapi juga sebagai motivator dan pembimbing yang membentuk karakter santri secara holistik.Penelitian ini diharapkan dapat menjadi acuan dalam pengembangan program pembinaan karakter di pesantren serta menjadi referensi bagi lembaga pendidikan Islam lainnya dalam membentuk generasi yang mandiri dan berakhlak mulia.